Qur'anic Language-Based Arabic Learning: A Qualitative Case Study at Markaz Al-Hijaz Jakarta - Aflah Ulima Rusyda; Fairuz Subakir Ahmad (Abjadia : International Journal of Education, 2026)
Arabic language learning plays an important role in Islamic education as Arabic is the language of the Qur’an and Islamic sources of knowledge. The development of digital technology has also influenced Arabic language learning, including in online-based nonformal institutions. This study investigates how Qur’anic language-based Arabic learning is implemented and integrated into online Arabic instruction at Markaz Al-Hijaz Jakarta. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving five Arabic teachers from Indonesia and Saudi Arabia (n=5 teachers) and more than 200 learners from diverse educational and age backgrounds (n>200 learners). The findings show that learning activities are conducted online through Zoom and WhatsApp, enabling flexible participation from learners across different backgrounds. Qur’anic language is implemented through vocabulary, sentence structures, and expressions derived from Qur’anic texts to strengthen linguistic competence and religious understanding simultaneously. Online learning provides broader access and flexibility, although challenges remain, including limited interaction, differences in learners’ Arabic proficiency, and internet connectivity issues. This study concludes that Qur’anic language-based Arabic learning at Markaz Al-Hijaz Jakarta represents an integrative learning model that combines linguistic competence, religious values, and digital technology in contemporary Arabic language learning. The unique contribution of this study lies in highlighting how Qur’anic language can function as both a linguistic and spiritual foundation within online Arabic learning in nonformal educational settings.